Trabectedin for recurrent WHO grade 2 or 3 meningioma: A randomized phase II study of the EORTC Brain Tumor Group (EORTC-1320-BTG). Issue 5 (21st October 2021) - Preusser, Matthias; Silvani, Antonio; Le Rhun, Emilie; Soffietti, Riccardo; Lombardi, Giuseppe; Sepulveda, Juan Manuel; Brandal, Petter; Brazil, Lucy; Bonneville-Levard, Alice; Lorgis, Veronique; Vauleon, Elodie; Bromberg, Jacoline; et al.
Abstract: Background: No systemic treatment has been established for meningioma progressing after local therapies. Methods: This randomized, multicenter, open-label, phase II study included adult patients with recurrent WHO grade 2 or 3 meningioma. Patients were 2:1 randomly assigned to intravenous trabectedin (1.5 mg/m 2 every 3 weeks) or local standard of care (LOC). The primary endpoint was progression-free survival (PFS). Secondary endpoints comprised overall survival (OS), objective radiological response, safety, quality of life (QoL) assessment using the QLQ-C30 and QLQ-BN20 questionnaires, and we performed tissue-based exploratory molecular analyses. Results: Ninety patients were randomized (n = 29 in LOC, n = 61 in trabectedin arm). With 71 events, median PFS was 4.17 months in the LOC and 2.43 months in the trabectedin arm (hazard ratio [HR] = 1.42; 80% CI, 1.00-2.03; P = .294) with a PFS-6 rate of 29.1% (95% CI, 11.9%-48.8%) and 21.1% (95% CI, 11.3%-32.9%), respectively. Median OS was 10.61 months in the LOC and 11.37 months in the trabectedin arm (HR = 0.98; 95% CI, 0.54-1.76; P = .94). Grade ≥3 adverse events occurred in 44.4% of patients in the LOC and 59% of patients in the trabectedin arm. Enrolled patients had impeded global QoL and overall functionality and high fatigue before initiation of systemic therapy. DNA methylation class, performance status, presence of a relevant co-morbidity, steroid use, and right hemisphere involvement at baseline were independently associated with OS. Conclusions: Trabectedin did not improve PFS and OS and was associated with higher toxicity than LOC treatment in patients with non-benign meningioma. Tumor DNA methylation class is an independent prognostic factor for OS.